Critical success factors for a destination management system for South Africa - Goodwin, Catherine Elizabeth (My University, 2011)
Destination Management Systems (DMS) are considered to hold much promise in theory but have proven difficult to implement in reality. In general, destinations have failed to bring together stakeholders in a way that ensures sustainability of the system. This study explores the critical success factors for implementing a DMS in South Africa. This study is based on previous research by Frew and O’Connor (1999), who established a list of critical success factors for DMS implementations in England, Scotland, Ireland and Austria. The objective of this research was to determine whether these findings held for the South African case. In-depth, semi-structured interviews were used to obtain views of South African destination stakeholders including strategy consultants, destination management and marketing practitioners, IT service providers, tourism product owners and tourism suppliers. The main findings were that the critical success factors of previous research did hold for the South African case but these were supplemented by a number of additional factors reflecting the current reality. In addition, respondents agreed that for a DMS to succeed government would need to fund the project, but this project should be managed by the private sector. Finally, it was found that central government should consult the industry on a single universal tourism strategy to determine common goals for the public and private sectors
MBA - WBS
Keywords: Tourism; Destination management systems